Composite proton exchange membrane and preparation method thereof, membrane electrode and electrochemical device
By introducing non-perfluorosulfonic acid resin and perfluorosulfonic acid resin into the proton exchange membrane and controlling the EW value of the resin, a composite proton exchange membrane was designed, which solved the problem of large environmental pollution of the PFSA proton exchange membrane in the prior art, and achieved membrane electrode performance with high proton conductivity and stability.
Patent Information
- Application Number
- CN202410874832.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-02
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-07-02
AI Technical Summary
In existing proton exchange membrane fuel cells, the synthesis and production of perfluorosulfonic acid (PFSA) proton exchange membranes are highly polluted to the environment. How to maintain good proton conductivity while reducing the use of PFSA is a challenge.
The composite proton exchange film is designed, including a perfluorosulfonic acid resin layer and a non-perfluorosulfonic acid resin layer. The two layers are laminated and the film performance is optimized by controlling the equal value of the resin (EW value) so that the EW value of the perfluorosulfonic acid resin layer is greater than the EW value of the non-perfluorosulfonic acid resin layer.
It effectively reduces the amount of perfluorosulfonic acid resin, improves the environmental friendliness of the composite proton exchange membrane, and improves the proton conductivity and stability of the membrane, thereby improving the peak power density of the membrane electrode and the electrochemical performance of the electrochemical device.
Smart Images

Figure CN118630272B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of new energy technology, and in particular to a composite proton exchange membrane and a preparation method thereof, a membrane electrode and an electrochemical device. Background Art
[0002] Fuel cells can directly convert fuel into electrical energy through redox reactions. They are a highly efficient and environmentally friendly green new energy battery.
[0003] Proton exchange membrane fuel cell (PEMFC) is one of the most widely used fuel cells, which consists of membrane electrode, bipolar plate, current collector and other components. Among them, the proton exchange membrane is the most core component, which plays the role of transmitting protons. At present, perfluorosulfonic acid (PFSA) proton exchange membrane is the most common and commonly used proton exchange membrane. However, due to the great environmental pollution caused by the synthesis and production of PFSA, how to make the proton exchange membrane have better proton conductivity while minimizing the use of PFSA is a problem that needs to be further solved. Summary of the invention
[0004] The present application provides a composite proton exchange membrane and a preparation method thereof, a membrane electrode and an electrochemical device. The composite proton exchange membrane can have a better proton conductivity while reducing the use of perfluorosulfonic acid, so that when it is applied to the membrane electrode, it can effectively increase the peak power density of the membrane electrode and improve the electrochemical performance of the electrochemical device.
[0005] The embodiment of the present application is implemented as follows:
[0006] In a first aspect, the present application provides an example of a composite proton exchange membrane, comprising: a perfluorosulfonic acid resin layer and a non-perfluorosulfonic acid resin layer, wherein the non-perfluorosulfonic acid resin layer and the perfluorosulfonic acid resin layer are stacked, and the EW value of the perfluorosulfonic acid resin in the perfluorosulfonic acid resin layer is greater than the EW value of the non-perfluorosulfonic acid resin in the non-perfluorosulfonic acid resin layer.
[0007] The composite proton exchange membrane provided by the present application introduces non-perfluorosulfonic acid resin and perfluorosulfonic acid resin into the composite proton exchange membrane, and utilizes the EW value of the perfluorosulfonic acid resin to be greater than the EW value of the non-perfluorosulfonic acid resin. On the one hand, the amount of perfluorosulfonic acid resin used is effectively reduced, thereby improving the environmental friendliness of the composite proton exchange membrane. On the other hand, the proton conductivity and stability of the composite proton exchange membrane can be effectively improved, so that when the composite proton exchange membrane is applied to a membrane electrode with the perfluorosulfonic acid resin layer as the cathode side and the non-perfluorosulfonic acid resin layer as the anode side, the membrane electrode peak power density is effectively improved.
[0008] In some embodiments, the composite proton exchange membrane includes a porous reinforcement layer, wherein the porous reinforcement layer is located between the perfluorosulfonic acid resin layer and the non-perfluorosulfonic acid resin layer.
[0009] In some embodiments, the porous reinforcement layer has a first surface connected to the non-perfluorosulfonic acid resin layer and a second surface connected to the perfluorosulfonic acid resin layer, the first surface has first pores, the second surface has second pores, and at least some of the first pores are connected to the second pores.
[0010] In some embodiments, at least a portion of the first pores is filled with a non-perfluorosulfonic acid resin filling layer connected to the non-perfluorosulfonic acid resin layer, at least a portion of the second pores is filled with a perfluorosulfonic acid resin filling layer connected to the perfluorosulfonic acid resin layer, and at least a portion of the non-perfluorosulfonic acid resin filling layer is connected to at least a portion of the perfluorosulfonic acid resin filling layer.
[0011] In some embodiments, the composition of the non-perfluorosulfonic acid resin layer is the same as that of the non-perfluorosulfonic acid resin filling layer, and the composition of the perfluorosulfonic acid resin layer is the same as that of the perfluorosulfonic acid resin filling layer.
[0012] In some embodiments, the porous reinforcement layer satisfies one or more of (a1)-(a2):
[0013] (a1) the material of the porous reinforcement layer comprises at least one of expanded polytetrafluoroethylene, polyvinylidene fluoride, polyetheretherketone, and polyethylene;
[0014] (a2) The thickness of the porous reinforcement layer is 5 μm-10 μm.
[0015] In some embodiments, the composite proton exchange membrane is composed of a perfluorosulfonic acid resin layer and a non-perfluorosulfonic acid resin layer formed on any surface of the perfluorosulfonic acid resin layer.
[0016] In some embodiments, the thickness of the perfluorosulfonic acid resin layer is ≥ the thickness of the non-perfluorosulfonic acid resin layer.
[0017] Optionally, the thickness difference between the perfluorosulfonic acid resin layer and the non-perfluorosulfonic acid resin layer is ≤2 μm.
[0018] In some embodiments, the perfluorosulfonic acid resin layer has the same thickness as the non-perfluorosulfonic acid resin layer.
[0019] In some embodiments, the non-perfluorosulfonic acid resin includes at least one of a sulfonated polyimide, a sulfonated polysulfone, a sulfonated polybenzimidazole, and a sulfonated polyetheretherketone.
[0020] In some embodiments, the composite proton exchange membrane has a thickness of 10 μm to 30 μm.
[0021] In a second aspect, the present application provides an example of a method for preparing the composite proton exchange membrane provided in the first aspect of the present application, which comprises:
[0022] A step of laminating a perfluorosulfonic acid resin layer and a non-perfluorosulfonic acid resin layer.
[0023] The preparation method provided in the present application is easy to operate and facilitates large-scale production. At the same time, the prepared composite proton exchange membrane takes into account better environmental friendliness, proton conductivity and stability. When the composite proton exchange membrane is applied to the membrane electrode with a perfluorosulfonic acid resin layer as the cathode side and a non-perfluorosulfonic acid resin layer as the anode side, it is beneficial to improve the peak power density of the membrane electrode.
[0024] In some embodiments, the step of stacking the perfluorosulfonic acid resin layer and the non-perfluorosulfonic acid resin layer includes: obtaining a hydrophilically treated porous reinforcement layer;
[0025] Firstly, a first resin dispersion is applied to any one side of the porous reinforcement layer along the thickness direction, and after drying, a second resin dispersion is applied to the other side of the porous reinforcement layer along the thickness direction, and dried;
[0026] Among them, one of the first resin dispersion and the second resin dispersion is a non-perfluorosulfonic acid resin dispersion for forming a non-perfluorosulfonic acid resin layer, and the other is a perfluorosulfonic acid resin dispersion for forming a perfluorosulfonic acid resin layer.
[0027] In some embodiments, the mass percentage of the non-perfluorosulfonic acid resin in the dispersion of the non-perfluorosulfonic acid resin is 10%-20%; and / or,
[0028] The mass percentage of the perfluorosulfonic acid resin in the perfluorosulfonic acid resin dispersion is 10%-20%.
[0029] In the third aspect, the present application provides an example of a membrane electrode, which includes the composite proton exchange membrane provided in the first aspect of the present application, a cathode catalyst layer and an anode catalyst layer; wherein the cathode catalyst layer is formed on the surface of the perfluorosulfonic acid resin layer, and the anode catalyst layer is formed on the surface of the non-perfluorosulfonic acid resin layer.
[0030] The membrane electrode provided in the present application uses the perfluorosulfonic acid resin layer in the composite proton exchange membrane as the cathode side and the non-perfluorosulfonic acid resin layer as the anode side, which is beneficial to improving the peak power density of the membrane electrode.
[0031] In some embodiments, the cathode catalyst layer includes a first binder, the first binder includes a perfluorosulfonic acid resin; and / or,
[0032] The anode catalyst layer includes a second binder including a non-perfluorosulfonic acid resin.
[0033] In some embodiments, the first binder has the same composition as the perfluorosulfonic acid resin in the perfluorosulfonic acid resin layer; and / or the second binder has the same composition as the non-perfluorosulfonic acid resin in the non-perfluorosulfonic acid resin layer.
[0034] In some embodiments, the mass percentage of the first binder in the cathode catalyst layer is 1%-5%; and / or,
[0035] The mass percentage of the second binder in the anode catalyst layer is 1%-5%.
[0036] In a fourth aspect, the present application provides an electrochemical device, which includes the composite proton exchange membrane provided in the first aspect of the present application or the membrane electrode provided in the third aspect of the present application.
[0037] Among them, the electrochemical device includes a fuel cell, a PEM electrolysis device or a flow battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0039] Figure 1 A schematic diagram of the structure of a composite proton exchange membrane provided in some embodiments of the present application;
[0040] Figure 2 A schematic diagram of the structure of a composite proton exchange membrane provided in some embodiments of the present application;
[0041] Figure 3 This is a schematic diagram of the structure of the membrane electrode provided in this application.
[0042] Icon: 10-composite proton exchange membrane; 11-perfluorosulfonic acid resin layer; 12-non-perfluorosulfonic acid resin layer; 13-porous reinforcement layer; 131-first body; 132-second body; 20-membrane electrode; 21-cathode catalyst layer; 22-anode catalyst layer. DETAILED DESCRIPTION
[0043] The embodiments of the present application will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. In the examples, if specific conditions are not specified, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0044] In the description of this application, the term "and / or" is merely a term used to describe the association relationship between associated objects, indicating that three relationships may exist. For example, A and / or B may represent three situations: A exists alone, A and B exist at the same time, and B exists alone.
[0045] The following is a detailed description of the composite proton exchange membrane and its preparation method, membrane electrode and electrochemical device according to the embodiments of the present application:
[0046] like Figure 1 as well as Figure 2 As shown, the present application provides a composite proton exchange membrane 10, which includes: a perfluorosulfonic acid resin layer 11 and a non-perfluorosulfonic acid resin layer 12. The non-perfluorosulfonic acid resin layer 12 is stacked with the perfluorosulfonic acid resin layer 11, and the EW value of the perfluorosulfonic acid resin in the perfluorosulfonic acid resin layer 11 is greater than the EW value of the non-perfluorosulfonic acid resin in the non-perfluorosulfonic acid resin layer 12.
[0047] In the present application, the non-perfluorosulfonic acid resin is a polymer with a sulfonic acid group and a partially fluorinated main chain structure or a non-fluorinated main chain structure. Among them, the main chain of the non-perfluorosulfonic acid resin with a partially fluorinated main chain structure includes but is not limited to one or more of polyvinyl fluoride, polyvinylidene fluoride or ethylene-tetrafluoroethylene copolymer; the non-perfluorosulfonic acid resin with a non-fluorinated main chain structure includes but is not limited to at least one of sulfonated polyimide, sulfonated polysulfone, sulfonated polybenzimidazole and sulfonated polyetheretherketone.
[0048] The structural formula of perfluorosulfonic acid resin (PFSA) is as follows:
[0049] Wherein m and n are respectively greater than or equal to 1. For example, the perfluorosulfonic acid resin includes but is not limited to any one of NR50 of DuPont, PW-79S of Solvay (Chemical) Shanghai Co., Ltd., and F-9010 of Asahi Glass Co., Ltd., Japan, or a mixture of two or more thereof.
[0050] "EW value" is material equivalent, which is a parameter for measuring the density of sulfonic acid groups. It represents the mass of the membrane required to contain 1 mol of hydrogen ions, and the unit is g / mol. The smaller the EW value, the greater the density of sulfonic acid groups in the membrane, and the better the conductivity of the membrane. Among them, the EW value of the perfluorosulfonic acid resin in the perfluorosulfonic acid resin layer 11 is greater than the EW value of the non-perfluorosulfonic acid resin in the non-perfluorosulfonic acid resin layer 12, that is, the conductivity of the perfluorosulfonic acid resin layer 11 is less than the conductivity of the non-perfluorosulfonic acid resin layer 12, and the ion exchange capacity of the perfluorosulfonic acid resin layer 11 is better than the ion exchange capacity of the non-perfluorosulfonic acid resin layer 12, so that the composite proton exchange membrane 10 has good proton exchange performance.
[0051] The stacking arrangement of the non-perfluorosulfonic acid resin layer 12 and the perfluorosulfonic acid resin layer 11 refers to direct compounding of the two, or compounding through an intermediate medium. Regardless of the arrangement, it can be understood that at least a portion of the surface of the non-perfluorosulfonic acid resin layer 12 is connected to at least a portion of the surface of the perfluorosulfonic acid resin layer 11, thereby utilizing the sulfonic acid group to transfer protons.
[0052] The composite proton exchange membrane 10 provided in the present application, through the above-mentioned configuration, can effectively reduce the amount of perfluorosulfonic acid resin used, improve the environmental friendliness of the composite proton exchange membrane 10, and can effectively improve the proton conductivity and stability of the composite proton exchange membrane 10. The composite proton exchange membrane 10 is applied to the membrane electrode 20 with the perfluorosulfonic acid resin layer 11 as the cathode side and the non-perfluorosulfonic acid resin layer 12 as the anode side, which is conducive to improving the peak power density of the membrane electrode 20.
[0053] like Figure 1 As shown, in some optional embodiments, the composite proton exchange membrane 10 includes a porous reinforcement layer 13 , and the porous reinforcement layer 13 is located between the perfluorosulfonic acid resin layer 11 and the non-perfluorosulfonic acid resin layer 12 .
[0054] The porous reinforcing layer 13 is a layer having a plurality of micropores therein and having a structure in which these micropores are connected, and a gas or a liquid can pass through from one surface (the first surface or the second surface) to reach the other surface in the thickness direction thereof.
[0055] In some optional embodiments, the porous reinforcement layer 13 has a first surface connected to the non-perfluorosulfonic acid resin layer 12 and a second surface connected to the perfluorosulfonic acid resin layer 11, the first surface has first pores, the second surface has second pores, and at least part of the first pores are connected to the second pores.
[0056] The porous reinforcement layer 13 is introduced to improve the mechanical properties of the composite proton exchange membrane 10 .
[0057] In some optional embodiments, at least a portion of the first pores is filled with a non-perfluorosulfonic acid resin filling layer connected to the non-perfluorosulfonic acid resin layer 12, and at least a portion of the second pores is filled with a perfluorosulfonic acid resin filling layer connected to the perfluorosulfonic acid resin layer 11, wherein at least a portion of the non-perfluorosulfonic acid resin filling layer is connected to at least a portion of the perfluorosulfonic acid resin filling layer.
[0058] In order to facilitate intuitive understanding, at least part of the first pores are filled with a non-perfluorosulfonic acid resin filling layer connected to the non-perfluorosulfonic acid resin layer 12, at least part of the second pores are filled with a perfluorosulfonic acid resin filling layer connected to the perfluorosulfonic acid resin layer 11, and the non-perfluorosulfonic acid resin filling layer is connected to the perfluorosulfonic acid resin filling layer. Figure 1 The filled porous reinforcement layer 13 is divided into a first body 131 and a second body 132 connected to each other along the thickness direction. The first body 131 has a second surface, and the second surface has second pores filled with a perfluorosulfonic acid resin filling layer. The second body 132 has a first surface, and the first surface has first pores filled with a non-perfluorosulfonic acid resin filling layer.
[0059] By controlling that at least part of the first pores are filled with a non-perfluorosulfonic acid resin filling layer connected to the non-perfluorosulfonic acid resin layer 12, at least part of the second pores are filled with a perfluorosulfonic acid resin filling layer connected to the perfluorosulfonic acid resin layer 11, and at least part of the non-perfluorosulfonic acid resin filling layer is connected to at least part of the perfluorosulfonic acid resin filling layer, it is not only beneficial to make the interface of the porous reinforcement layer 13 and the non-perfluorosulfonic acid resin layer 12 and the non-perfluorosulfonic acid resin layer 12 have good bonding, thereby reducing the contact resistance of the composite proton exchange membrane 10, which is beneficial to improving the chemical and mechanical properties of the composite proton exchange membrane 10, but also the structure of the membrane is not easily destroyed and has excellent stability, and it is also beneficial to improve the selectivity of the composite proton exchange membrane 10.
[0060] The components of the non-perfluorosulfonic acid resin layer 12 and the non-perfluorosulfonic acid resin filling layer may be the same or different, and the components of the perfluorosulfonic acid resin layer 11 and the perfluorosulfonic acid resin filling layer may be the same or different.
[0061] In some optional embodiments, the composition of the non-perfluorosulfonic acid resin layer 12 is the same as that of the non-perfluorosulfonic acid resin filling layer, and the composition of the perfluorosulfonic acid resin layer 11 is the same as that of the perfluorosulfonic acid resin filling layer. The preparation is convenient and the composite proton exchange membrane 10 has good performance.
[0062] In some optional embodiments, the porous reinforcement layer 13 satisfies one or more of (a1)-(a2):
[0063] (a1) The material of the porous reinforcement layer 13 includes at least one of expanded polytetrafluoroethylene (e-PTFE), polyvinylidene fluoride, polyetheretherketone, and polyethylene;
[0064] The above materials have good mechanical properties, which is beneficial to improving the mechanical properties of the composite proton exchange membrane 10 .
[0065] Optionally, the porous reinforcement layer 13 is made of expanded polytetrafluoroethylene.
[0066] (a2) The thickness of the porous reinforcing layer 13 is 5 μm to 10 μm.
[0067] The above range is beneficial to improving the mechanical properties of the composite proton exchange membrane 10 and preventing the composite proton exchange membrane 10 from being too thick.
[0068] Exemplarily, the thickness of the porous reinforcement layer 13 is any value of 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, and 10 μm, or is between any two values.
[0069] See also Figure 2In some optional embodiments, the composite proton exchange membrane 10 is composed of a perfluorosulfonic acid resin layer 11 and a non-perfluorosulfonic acid resin layer 12 formed on any surface of the perfluorosulfonic acid resin layer 11 .
[0070] The above-mentioned composite proton exchange membrane 10 has a simple structure and is easy to prepare, which is beneficial to effectively reduce the usage of perfluorosulfonic acid resin and improve the environmental friendliness of the composite proton exchange membrane 10. At the same time, when the composite proton exchange membrane 10 is applied to the membrane electrode 20 with the perfluorosulfonic acid resin layer 11 as the cathode side and the non-perfluorosulfonic acid resin layer 12 as the anode side, it is beneficial to improve the peak power density of the membrane electrode 20.
[0071] Because the mechanical strength of non-perfluorosulfonic acid resin is weaker than that of perfluorosulfonic acid resin.
[0072] Therefore, in some optional embodiments, the thickness of the perfluorosulfonic acid resin layer 11 is greater than or equal to the thickness of the non-perfluorosulfonic acid resin layer 12 .
[0073] The thickness of the perfluorosulfonic acid resin layer 11 refers to the straight-line distance between one side of the perfluorosulfonic acid resin layer 11 away from the porous reinforcing layer 13 and the second side of the porous reinforcing layer 13, and the thickness of the non-perfluorosulfonic acid resin layer 12 refers to the straight-line distance between one side of the non-perfluorosulfonic acid resin layer 12 away from the porous reinforcing layer 13 and the first side of the porous reinforcing layer 13.
[0074] The above configuration is helpful to improve the mechanical strength of the composite proton exchange membrane 10 .
[0075] Optionally, the thickness difference between the perfluorosulfonic acid resin layer 11 and the non-perfluorosulfonic acid resin layer 12 is ≤ 2 μm.
[0076] If the thickness difference between the perfluorosulfonic acid resin layer 11 and the non-perfluorosulfonic acid resin layer 12 is too large, it is easy to cause the proton conductivity of the composite proton exchange membrane 10 to be too poor and affect its mechanical properties. Therefore, by limiting the thickness difference between the perfluorosulfonic acid resin layer 11 and the non-perfluorosulfonic acid resin layer 12 to within the above range, it is beneficial for the composite proton exchange membrane 10 to have both better mechanical strength and better proton conductivity.
[0077] Illustratively, the thickness difference between the perfluorosulfonic acid resin layer 11 and the non-perfluorosulfonic acid resin layer 12 is any value of 2 μm, 1.5 μm, 1.2 μm, 1 μm, 0.7 μm, 0.5 μm, 0.3 μm, 0 μm, or between any two values.
[0078] In some optional embodiments, the thickness of the perfluorosulfonic acid resin layer 11 and the non-perfluorosulfonic acid resin layer 12 are the same.
[0079] Within the above range, the composite proton exchange membrane 10 has both better mechanical strength and better proton conductivity.
[0080] In some optional embodiments, the non-perfluorosulfonic acid resin includes at least one of sulfonated polyimide, sulfonated polysulfone, sulfonated polybenzimidazole and sulfonated polyetheretherketone.
[0081] The above-mentioned non-perfluorosulfonic acid resin and perfluorosulfonic acid resin have a good combination effect, which is beneficial to effectively improve the proton conductivity of the composite proton exchange membrane 10 obtained while having better mechanical strength.
[0082] In some optional embodiments, the composite proton exchange membrane 10 has a thickness of 10-30 μm.
[0083] Exemplarily, the thickness of the composite proton exchange membrane 10 is any value of 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, or between any two values.
[0084] It is understood that the thickness of the porous reinforcement layer 13 is less than the thickness of the composite proton exchange membrane 10. It is understood that when the composite proton exchange membrane 10 does not include the porous reinforcement layer 13, better mechanical properties can be obtained by increasing the thickness of the composite proton exchange membrane 10.
[0085] The present application also provides a method for preparing the composite proton exchange membrane 10, which comprises:
[0086] A step of laminating the perfluorosulfonic acid resin layer 11 and the non-perfluorosulfonic acid resin layer 12 .
[0087] The preparation method provided in the present application is easy to operate and facilitates large-scale production. At the same time, the prepared composite proton exchange membrane 10 takes into account better environmental friendliness, proton conductivity and stability. When the composite proton exchange membrane 10 is applied to the membrane electrode 20 with the perfluorosulfonic acid resin layer 11 as the cathode side and the non-perfluorosulfonic acid resin layer 12 as the anode side, it is beneficial to improve the peak power density of the membrane electrode 20.
[0088] In some optional embodiments, the step of stacking the perfluorosulfonic acid resin layer 11 and the non-perfluorosulfonic acid resin layer 12 includes: obtaining a porous reinforcement layer 13 after hydrophilic treatment;
[0089] First, a first resin dispersion is applied to any one surface of the porous reinforcement layer 13 along the thickness direction, and after drying, a second resin dispersion is applied to the other surface of the porous reinforcement layer 13 along the thickness direction, and dried;
[0090] Among them, one of the first resin dispersion and the second resin dispersion is a non-perfluorosulfonic acid resin dispersion for forming the non-perfluorosulfonic acid resin layer 12, and the other is a perfluorosulfonic acid resin dispersion for forming the perfluorosulfonic acid resin layer 11. It can be understood that the porous reinforcing layer 13, such as e-PTFE, has low surface free energy and high water resistance, so in order to facilitate the filling of perfluorosulfonic acid resin and non-perfluorosulfonic acid resin into the pores of the porous reinforcing layer 13. The method of modifying the surface of the porous reinforcing layer 13 to make it hydrophilic (hydrophilization treatment) is well known, including but not limited to plasma treatment, corona treatment, etc.
[0091] It is understandable that the order of coating the non-perfluorosulfonic acid resin dispersion and the perfluorosulfonic acid resin dispersion during the preparation process is not limited and can be selected according to actual needs.
[0092] The coating method may be a casting method or a spraying method, which is not limited here. By coating with a resin dispersion, the pores on one side of the porous reinforcing layer 13 (i.e., the first pores) can be filled with non-perfluorosulfonic acid resin, and the pores on the other side (i.e., the second pores) can be filled with perfluorosulfonic acid resin.
[0093] It can be understood that the non-perfluorosulfonic acid resin dispersion here is used to form the non-perfluorosulfonic acid resin layer 12 and the non-perfluorosulfonic acid resin filling layer, and the perfluorosulfonic acid resin dispersion here is used to form the perfluorosulfonic acid resin layer 11 and the perfluorosulfonic acid resin filling layer, that is, the equivalent of the fluorosulfonic acid resin in the perfluorosulfonic acid resin dispersion is greater than the equivalent of the non-fluorosulfonic acid resin in the non-fluorosulfonic acid resin dispersion.
[0094] In addition, in some other optional embodiments, the step of stacking the perfluorosulfonic acid resin layer 11 and the non-perfluorosulfonic acid resin layer 12 includes: firstly applying the first resin dispersion on the surface of the smooth substrate, drying to obtain the first resin layer, applying the second resin dispersion on the surface of the first resin layer, and drying to separate the composite resin layer from the substrate; wherein, in the first resin dispersion and the second resin dispersion, either one is a non-perfluorosulfonic acid resin dispersion for forming the non-perfluorosulfonic acid resin layer 12, and the other is a perfluorosulfonic acid resin dispersion for forming the perfluorosulfonic acid resin layer 11. Regardless of the above-mentioned preparation method, in order to smoothly prepare the perfluorosulfonic acid resin layer 11 and the non-perfluorosulfonic acid resin layer 12, and also to facilitate subsequent drying, in some optional embodiments, the mass percentage of the non-perfluorosulfonic acid resin in the non-perfluorosulfonic acid resin dispersion is 10-20%, and / or, the mass percentage of the perfluorosulfonic acid resin in the perfluorosulfonic acid resin dispersion is 10-20%.
[0095] The solvent in the non-perfluorosulfonic acid resin dispersion includes but is not limited to N,N-dimethylformamide (DMF), and can also be water alcohol. The solvent in the perfluorosulfonic acid resin dispersion includes but is not limited to N,N-dimethylformamide (DMF) or tetrahydrofuran (THF), and can also be water alcohol. Water alcohol refers to a mixture of alcohol and water, usually refers to an ethanol aqueous solution obtained by mixing water and ethanol in a certain proportion.
[0096] Optionally, the mass percentage of the non-perfluorosulfonic acid resin in the non-perfluorosulfonic acid resin dispersion is the same as the mass percentage of the perfluorosulfonic acid resin in the perfluorosulfonic acid resin dispersion.
[0097] By controlling the above mass percentages to be the same, it is convenient to adopt the same preparation parameters to prepare the perfluorosulfonic acid resin layer 11 and the non-perfluorosulfonic acid resin layer 12 with the same thickness.
[0098] It should be noted that, in addition to controlling the mass percentage of the dispersion, the thickness during coating can also be controlled to control the thickness of the final perfluorosulfonic acid resin layer 11 and the non-perfluorosulfonic acid resin layer 12, which is not limited here.
[0099] like Figure 3 As shown, the present application also provides a membrane electrode 20 , which includes the above-mentioned composite proton exchange membrane 10 , a cathode catalyst layer 21 and an anode catalyst layer 22 .
[0100] The cathode catalyst layer 21 is formed on the surface of the perfluorosulfonic acid resin layer 11 , and the anode catalyst layer 22 is formed on the surface of the non-perfluorosulfonic acid resin layer 12 .
[0101] It is understandable that the cathode catalyst layer 21 includes a cathode catalyst, and the anode catalyst layer 22 includes an anode catalyst. The specific cathode catalyst and anode catalyst can be selected according to the electrochemical device actually used for the membrane electrode 20 and actual needs, and are not limited here.
[0102] The membrane electrode 20 provided in the present application uses the perfluorosulfonic acid resin layer 11 in the composite proton exchange membrane 10 as the cathode side and the non-perfluorosulfonic acid resin layer 12 as the anode side, which is beneficial to improving the peak power density of the membrane electrode 20.
[0103] In some optional embodiments, the cathode catalyst layer 21 includes a first binder, and the first binder includes a perfluorosulfonic acid resin; and / or,
[0104] The anode catalyst layer 22 includes a second binder including a non-perfluorosulfonic acid resin.
[0105] The first binder includes perfluorosulfonic acid resin, which is beneficial to improving the bonding strength between the cathode catalyst layer 21 and the perfluorosulfonic acid resin layer 11. The second binder includes non-perfluorosulfonic acid resin, which is beneficial to improving the bonding strength between the anode catalyst layer 22 and the non-perfluorosulfonic acid resin layer 12. The combined effect effectively improves the stability of the membrane electrode 20.
[0106] It is understandable that the components of the perfluorosulfonic acid resin in the first binder and the perfluorosulfonic acid resin in the fluorosulfonic acid resin layer may be different or the same.
[0107] In some optional embodiments, the first binder has the same composition as the perfluorosulfonic acid resin in the perfluorosulfonic acid resin layer 11 , which is beneficial to further improve the interface stability between the cathode catalyst layer 21 and the perfluorosulfonic acid resin layer 11 .
[0108] It is understandable that the components of the perfluorosulfonic acid resin in the second binder and the perfluorosulfonic acid resin in the fluorosulfonic acid resin layer may be different or the same.
[0109] In some optional embodiments, the second binder has the same composition as the non-perfluorosulfonic acid resin in the non-perfluorosulfonic acid resin layer 12 , which is beneficial to further improve the interface stability between the anode catalyst layer 22 and the non-perfluorosulfonic acid resin layer 12 .
[0110] In some optional embodiments, the mass percentage of the first binder in the cathode catalyst layer 21 is 1-5%; and / or the mass percentage of the second binder in the anode catalyst layer 22 is 1-5%.
[0111] By controlling the contents of the first binder and the second binder within the above range, it is beneficial to form the cathode catalyst layer 21 and the cathode catalyst layer 21, and the electrochemical performance after film formation is good.
[0112] The present application also provides an electrochemical device, which includes the composite proton exchange membrane 10 or the membrane electrode 20 .
[0113] Among them, the electrochemical device includes a fuel cell, a PEM electrolysis device or a flow battery.
[0114] The composite proton exchange membrane 10 and its preparation method, membrane electrode 20 and electrochemical device of the present application are further described in detail below in conjunction with embodiments.
[0115] In the following examples and comparative examples, the thickness of e-PTFE is 7 μm and the porosity is 90%.
[0116] Example 1
[0117] Weigh 20g of perfluorosulfonic acid (PFSA) resin and add it to a mixed solvent of 80g of ethanol and 20g of deionized water. Then put the mixed solution into an autoclave and react for 24h at a temperature of 200°C and a rotation speed of 500r / min to dissolve the PFSA resin to obtain a perfluorosulfonic acid resin dispersion.
[0118] 20 g of sulfonated polyimide resin was weighed and added into 100 g of THF solvent. The mixture was reacted for 3 h at room temperature and a rotation speed of 500 r / min to dissolve the resin, thereby obtaining a sulfonated polyimide resin dispersion (ie, a non-perfluorosulfonic acid resin dispersion).
[0119] Using the casting method, on the surface of the hydrophilic e-PTFE, a perfluorosulfonic acid resin dispersion is scraped on one surface of the e-PTFE using a four-sided coater with a height of 200 μm, and then dried to obtain a perfluorosulfonic acid resin layer composited on the surface of the e-PTFE. Using a four-sided coater with a height of 200 μm, a sulfonated polyimide resin dispersion is scraped on the other side of the e-PTFE, and then dried to obtain a non-perfluorosulfonic acid resin layer composited on the surface of the e-PTFE.
[0120] Example 2
[0121] The only difference between it and Example 1 is that: 20g of perfluorosulfonic acid (PFSA) resin is weighed and added to a mixed solvent of 160g of ethanol and 40g of deionized water, and then the mixed solution is placed in an autoclave, and reacted for 24h at a temperature of 200°C and a rotation speed of 500r / min to dissolve, thereby obtaining a perfluorosulfonic acid resin dispersion.
[0122] 20 g of sulfonated polyimide resin was weighed and added into 200 g of THF solvent. The mixture was reacted for 3 h at room temperature and a rotation speed of 500 r / min to dissolve the resin, thereby obtaining a sulfonated polyimide resin dispersion (ie, a non-perfluorosulfonic acid resin dispersion).
[0123] Example 3
[0124] The difference between it and Example 1 is only that:
[0125] Weigh 20 g of sulfonated polyimide resin, add it into 200 g of THF solvent, react for 2-3 hours at room temperature and a rotation speed of 500 r / min to dissolve, and obtain a sulfonated polyimide resin dispersion (ie, a non-perfluorosulfonic acid resin dispersion).
[0126] Using the casting method, on the surface of the hydrophilic e-PTFE, a perfluorosulfonic acid resin dispersion is scraped on one surface of the e-PTFE using a four-sided coater with a height of 300 μm, and then dried to obtain a perfluorosulfonic acid resin layer composited on the surface of the e-PTFE. Using a four-sided coater with a height of 100 μm, a sulfonated polyimide resin dispersion is scraped on the other side of the e-PTFE, and then dried to obtain a non-perfluorosulfonic acid resin layer composited on the surface of the e-PTFE.
[0127] Example 4
[0128] The difference between it and Example 1 is only that:
[0129] Sulfonated polyetheretherketone was used to replace the sulfonated polyimide resin. The above steps were repeated to prepare the composite membrane.
[0130] Example 5
[0131] The difference between it and Example 1 is:
[0132] Without using ePTFE material as the porous reinforcement layer, a layer of 200 μm thick perfluorosulfonic acid resin solution was directly scraped on the surface of the smooth glass substrate, and the perfluorosulfonic acid resin layer was obtained after drying. Then, a layer of 200 μm thick sulfonated polyimide resin solution was scraped on the surface of the perfluorosulfonic acid resin layer and dried.
[0133] Comparative Example 1
[0134] The difference between it and Example 1 is only that:
[0135] Using the casting method, on the surface of the hydrophilic e-PTFE, a perfluorosulfonic acid resin dispersion was scraped onto one surface of the e-PTFE using a four-sided coater with a height of 200 μm. After drying, the perfluorosulfonic acid resin dispersion was scraped onto the other side of the e-PTFE using a four-sided coater with a height of 200 μm. After drying, a perfluorosulfonic acid resin composite proton exchange membrane with a total thickness of 15 μm was obtained, wherein the thickness of the perfluorosulfonic acid resin layer on one side was 4 μm.
[0136] Test Example 1
[0137] The thickness, mechanical properties and proton conductivity of the composite proton exchange membranes prepared in each embodiment and comparative example 1 were tested.
[0138] The thickness test is obtained by using a thickness gauge in the film thickness uniformity test mentioned in GB / T 20042.3-2023, and the thickness gauge accuracy is not less than 0.1 micron.
[0139] The composite proton exchange membranes prepared in each embodiment and comparative example 1 were used to prepare membrane electrodes and used in a single fuel cell. A single fuel cell test was performed at 70°C with 100% RH humidified H2 / O2. In the single cell, the active catalytic area of all membranes was 4 cm 2 The anode catalyst layer 22 includes an anode catalyst and a perfluorosulfonic acid resin, and the cathode catalyst includes a cathode catalyst powder and a sulfonated polyimide resin or a sulfonated polyetheretherketone (the cathode side uses a non-perfluorosulfonic acid resin on the cathode side as a binder), wherein the mass ratio of the anode catalyst and the perfluorosulfonic acid resin in the anode catalyst layer is the same as the mass ratio of the cathode catalyst and the perfluorosulfonic acid resin in the cathode catalyst. The anode and cathode catalyst powders are commercial TEC10EA50E Pt / C (50wt% Pt) catalyst powders, and the anode catalyst layer loading is 0.2mg cm -2 , the cathode catalyst layer loading is 0.4 mg cm -2 In the PEMFC single cell corresponding to each embodiment, the anode catalyst layer is formed on the surface of the non-perfluorosulfonic acid resin layer, and the cathode catalyst layer is formed on the surface of the perfluorosulfonic acid resin layer.
[0140] The PEMFC single cell is composed of stainless steel as end plates and flow field, silicone rubber sheet as sealant and MEA. In the polarization test, high purity and 100% RH humidified hydrogen and oxygen were fed to the anode and cathode working at 70°C at flow rates of 50 and 100 standard cubic centimeters per minute (SCCM), respectively. A single cell was tested in the PEMFC test station, and the back pressure gauge reading of the two electrodes was 0.5 bar. The peak power density of the membrane electrode corresponding to each embodiment and comparative example 1 is shown in Table 1.
[0141] Table 1 Test results
[0142]
[0143]
[0144] According to Table 1, after the composite proton exchange membrane provided by the present application is applied to the membrane electrode, the peak power density of the membrane electrode is effectively improved compared with the comparative lithium 1, and the peak power density of the membrane electrode of the electrochemical performance of the electrochemical device is improved. It should be noted that although the mechanical properties of the non-perfluorosulfonic acid resin are slightly lower than those of the perfluorosulfonic acid resin, when the thickness of the composite proton exchange membrane is low (≤16μm), its tensile strength depends more on the strength of the ePTFE. At this time, the resin has little effect on its tensile strength. Therefore, when the above-mentioned embodiments and comparative examples use the same ePTFE with the same thickness, the tensile strengths of Embodiment 1 and Comparative Example 1 are the same.
[0145] It can be seen from Examples 1-4 that the thickness of the perfluorosulfonic acid resin layer is the same as that of the non-perfluorosulfonic acid resin layer, which is beneficial to improving the proton conductivity and has little effect on the tensile strength, and is more beneficial to improving the membrane electrode peak power density.
[0146] It can be seen from Examples 1 and 5 that the introduction of ePTFE can effectively enhance the tensile strength of the composite proton exchange membrane, and can effectively reduce the usage of perfluorosulfonic acid resin and non-perfluorosulfonic acid resin and reduce the production cost under the premise that the peak power density of the membrane electrode is not much different.
[0147] In summary, the composite proton exchange membrane and its preparation method, membrane electrode and electrochemical device provided in the present application can have better proton conductivity while reducing the use of perfluorosulfonic acid, so that after being applied to the membrane electrode, it can effectively improve the peak power density of the membrane electrode and improve the electrochemical performance of the electrochemical device.
[0148] The above are only specific embodiments of the present application and are not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A composite proton exchange membrane, characterized in that: include: a perfluorosulfonic acid resin layer; as well as a non-perfluorosulfonic acid resin layer, stacked with the perfluorosulfonic acid resin layer; wherein the EW value of the perfluorosulfonic acid resin in the perfluorosulfonic acid resin layer is greater than the EW value of the non-perfluorosulfonic acid resin in the non-perfluorosulfonic acid resin layer; The non-perfluorinated sulfonic acid resin is a polymer having a sulfonic acid group and a partially fluorinated main chain structure or a non-fluorinated main chain structure.
2. The composite proton exchange membrane according to claim 1, characterized in that: The composite proton exchange membrane comprises a porous reinforcement layer, and the porous reinforcement layer is located between the perfluorosulfonic acid resin layer and the non-perfluorosulfonic acid resin layer.
3. The composite proton exchange membrane according to claim 2, characterized in that: The porous reinforcement layer has a first surface connected to the non-perfluorosulfonic acid resin layer and a second surface connected to the perfluorosulfonic acid resin layer, the first surface has first pores, the second surface has second pores, and at least part of the first pores are connected to the second pores.
4. The composite proton exchange membrane according to claim 3, characterized in that: At least part of the first pores is filled with a non-perfluorosulfonic acid resin filling layer connected to the non-perfluorosulfonic acid resin layer, at least part of the second pores is filled with a perfluorosulfonic acid resin filling layer connected to the perfluorosulfonic acid resin layer, and at least part of the non-perfluorosulfonic acid resin filling layer is connected to at least part of the perfluorosulfonic acid resin filling layer.
5. The composite proton exchange membrane according to claim 4, characterized in that: The composition of the non-perfluorosulfonic acid resin layer is the same as that of the non-perfluorosulfonic acid resin filling layer, and the composition of the perfluorosulfonic acid resin layer is the same as that of the perfluorosulfonic acid resin filling layer.
6. The composite proton exchange membrane according to claim 2, characterized in that: The porous reinforcement layer satisfies one or more of (a1)-(a2): (a1) the material of the porous reinforcement layer includes at least one of expanded polytetrafluoroethylene, polyvinylidene fluoride, polyetheretherketone, and polyethylene; (a2) The thickness of the porous reinforcement layer is 5 μm to 10 μm.
7. The composite proton exchange membrane according to claim 1, characterized in that: The composite proton exchange membrane is composed of a perfluorosulfonic acid resin layer and a non-perfluorosulfonic acid resin layer formed on any surface of the perfluorosulfonic acid resin layer.
8. The composite proton exchange membrane according to any one of claims 1 to 7, characterized in that: The thickness of the perfluorosulfonic acid resin layer is greater than or equal to the thickness of the non-perfluorosulfonic acid resin layer.
9. The composite proton exchange membrane according to claim 8, characterized in that: The thickness difference between the perfluorosulfonic acid resin layer and the non-perfluorosulfonic acid resin layer is ≤2 μm.
10. The composite proton exchange membrane according to any one of claims 1 to 7, characterized in that: The perfluorosulfonic acid resin layer and the non-perfluorosulfonic acid resin layer have the same thickness.
11. The composite proton exchange membrane according to any one of claims 1 to 7, characterized in that: The non-perfluorosulfonic acid resin includes at least one of sulfonated polyimide, sulfonated polysulfone, sulfonated polybenzimidazole and sulfonated polyetheretherketone.
12. The composite proton exchange membrane according to any one of claims 1 to 7, characterized in that: The composite proton exchange membrane has a thickness of 10 μm-30 μm.
13. The method for preparing a composite proton exchange membrane according to any one of claims 1 to 12, characterized in that: include: The step of laminating the perfluorosulfonic acid resin layer and the non-perfluorosulfonic acid resin layer.
14. The preparation method according to claim 13, characterized in that: The step of stacking the perfluorosulfonic acid resin layer and the non-perfluorosulfonic acid resin layer comprises: Obtaining a porous reinforcement layer after hydrophilic treatment; Firstly, a first resin dispersion is applied to any one surface of the porous reinforcement layer along the thickness direction, and after drying, a second resin dispersion is applied to the other surface of the porous reinforcement layer along the thickness direction, and dried; Among them, one of the first resin dispersion and the second resin dispersion is a non-perfluorosulfonic acid resin dispersion for forming the non-perfluorosulfonic acid resin layer, and the other is a perfluorosulfonic acid resin dispersion for forming the perfluorosulfonic acid resin layer.
15. The preparation method according to claim 14, characterized in that: The mass percentage of the non-perfluorosulfonic acid resin in the dispersion of the non-perfluorosulfonic acid resin is 10%-20%; and / or, The mass percentage of the perfluorosulfonic acid resin in the perfluorosulfonic acid resin dispersion is 10%-20%.
16. A membrane electrode, characterized in that: Comprising the composite proton exchange membrane according to any one of claims 1 to 12, a cathode catalyst layer and an anode catalyst layer; The cathode catalyst layer is formed on the surface of the perfluorosulfonic acid resin layer, and the anode catalyst layer is formed on the surface of the non-perfluorosulfonic acid resin layer.
17. The membrane electrode according to claim 16, characterized in that: The cathode catalyst layer includes a first binder, wherein the first binder includes a perfluorosulfonic acid resin; and / or, The anode catalyst layer includes a second binder including a non-perfluorosulfonic acid resin.
18. The membrane electrode according to claim 17, characterized in that: The first binder has the same component as the perfluorosulfonic acid resin in the perfluorosulfonic acid resin layer; and / or the second binder has the same component as the non-perfluorosulfonic acid resin in the non-perfluorosulfonic acid resin layer.
19. The membrane electrode according to claim 17, characterized in that: The mass percentage of the first binder in the cathode catalyst layer is 1%-5%; and / or, The mass percentage of the second binder in the anode catalyst layer is 1%-5%.
20. An electrochemical device, characterized in that: A composite proton exchange membrane comprising any one of claims 1 to 12 or a membrane electrode according to any one of claims 16 to 19; Wherein, the electrochemical device includes a fuel cell, a PEM electrolysis device or a flow battery.
Citation Information
Patent Citations
Preparation of multi-layer composite proton exchange membrane, membrane and application of membrane
CN107994244A
Asymmetric polymer electrolyte composite membrane forfuel cell, method to prepare the same, non-homogeneouspolymer electrolyte composite membrane for fuel celland method to prepare the same
KR1020060083374A